ANALISIS SEMIOTIKA REPRESENTASI PERSAHABATAN DALAM FILM “HUGO” - Anofrina, Harry; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
coincidence factor take part in the friendships . It takes a long process and full of twistsand turns in achieving the goal. This friendships process and symbols which arerepresentated in “Hugo“ film. Movies is one form of visualization of human thoughttowards surrounding reality. In this case , the authors formulate the problem asfollows: "How Friendship Representated in the “Hugo“ film?" . The use of mark in thefilm can affect someone thaught in represent certain meaning, in this case the meaningthat representated is the mening that contained in friendships symbols.This kind of research is a qualitative descriptive research with semiotic data analysistechniques. Researchers use Triangle Meaning Charles Peirce to reveal the meaning offriendship representations which is contained in the signs that are in the movie Hugo.Data collection techniques used are observation, documentation and FGD (FocusGroup Discussion). This research aims to find out any kind of friendship sign thatcontained in Hugo Film, by analysing the signs in the films.Based on the analysis, it can be seen that friendship in the film Hugo divided into 3groups: utility, pleasure and virtue. (1) Utility, is a friendship because of the benefits,in this film Hugo friendship with Isabelle provides benefits not only for the two ofthem, but also for the people around him. (2) Pleasure, is friendship for pleasure , inthis film the friendship between Hugo and Isabelle provides enjoyable experience forthem through the adventure in solving the mystery of the automaton. (3) Virtue, truefriendship, in this film the friendship Hugo with Isabella not only just needed eachother and share the fun but also good to know and understand each other through joyand sorrow. Based on the results of the Focus Group Discussion group discussion(FGD) shows that friendship in the “Hugo” film consists of two types of friendshipswhich is fiendship because of the benefits and true friendship as seen on Hugofriendship with Isabelle.Keywords : Representation, Friendship, semiotic , Hugo Movie.